2015
DOI: 10.1038/srep12705
|View full text |Cite
|
Sign up to set email alerts
|

A Sensor Array Using Multi-functional Field-effect Transistors with Ultrahigh Sensitivity and Precision for Bio-monitoring

Abstract: Mechanically adaptive electronic skins (e-skins) emulate tactition and thermoception by cutaneous mechanoreceptors and thermoreceptors in human skin, respectively. When exposed to multiple stimuli including mechanical and thermal stimuli, discerning and quantifying precise sensing signals from sensors embedded in e-skins are critical. In addition, different detection modes for mechanical stimuli, rapidly adapting (RA) and slowly adapting (SA) mechanoreceptors in human skin are simultaneously required. Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 44 publications
(83 reference statements)
2
98
0
Order By: Relevance
“…Therefore, the direct integration of a piezoelectric polymer as a gate dielectric layer into the transistor is another approach for pressure sensors based on a piezo electric polymer. Tien and co-workers, [ 46,107 ] Trung et al, [ 77 ] and Kim et al [ 61 ] directly integrated a P(VDF-TrFE)/BaTiO 3 nanocomposite and P(VDF-TrFE) as gate dielectric layers with an OFET. The sensing mechanism of these devices based on the direct piezoelectric effect can be explained by the change of the remnant polarization ( P r ) or equivalent voltage ( V 0 ) inside the piezoelectric polymer under the external pressure that modulates the intensity of the charge accumulated at the semiconductor/dielectric interface leading to a changing source-drain read-out current.…”
Section: Piezoelectric Pressure Sensorsmentioning
confidence: 98%
See 3 more Smart Citations
“…Therefore, the direct integration of a piezoelectric polymer as a gate dielectric layer into the transistor is another approach for pressure sensors based on a piezo electric polymer. Tien and co-workers, [ 46,107 ] Trung et al, [ 77 ] and Kim et al [ 61 ] directly integrated a P(VDF-TrFE)/BaTiO 3 nanocomposite and P(VDF-TrFE) as gate dielectric layers with an OFET. The sensing mechanism of these devices based on the direct piezoelectric effect can be explained by the change of the remnant polarization ( P r ) or equivalent voltage ( V 0 ) inside the piezoelectric polymer under the external pressure that modulates the intensity of the charge accumulated at the semiconductor/dielectric interface leading to a changing source-drain read-out current.…”
Section: Piezoelectric Pressure Sensorsmentioning
confidence: 98%
“…The sensing mechanism of these devices based on the direct piezoelectric effect can be explained by the change of the remnant polarization ( P r ) or equivalent voltage ( V 0 ) inside the piezoelectric polymer under the external pressure that modulates the intensity of the charge accumulated at the semiconductor/dielectric interface leading to a changing source-drain read-out current. Furthermore, Tien et al [ 46 ] and Kim et al [ 61 ] demonstrated that a piezoelectric pressure sensor based on the P(VDF-TrFE)/BaTiO 3 nanocomposite can be used to measure static and dynamic pressure. Meanwhile, a piezoelectric pressure sensor is usually used to measure dynamic pressure only.…”
Section: Piezoelectric Pressure Sensorsmentioning
confidence: 98%
See 2 more Smart Citations
“…Three-dimensional (3D) structured conductive polymeric materials are promising for achieving highly flexible pressure sensors. In the last few years, various structures and materials have been developed to fabricate ultrasensitive pressure sensors that can effectively collect pressure stimuli in the low-pressure regime (<10 kPa) [11][12][13][14][15][16] . However, several obstacles limit the practical application of such sensors.…”
Section: Introductionmentioning
confidence: 99%